Effects of experimental warming on soil respiration and its components in an alpine meadow in the permafrost region of the Qinghai‐Tibet Plateau. (3rd November 2014) - Peng, F.; You, Q. G.; Xu, M. H.; Zhou, X. H.; Wang, T.; Guo, J.; Xue, X.
Summary The response of soil respiration (Rs) and its components (autotrophic [Ra] and heterotrophic respiration [Rh]) to climate warming is one of the uncertainties in ecosystem carbon (C) models. Here we conducted a warming experiment in an alpine meadow dominated by Koresbia in the permafrost region of the Qinghai‐Tibet Plateau (QTP) to examine effects of warming on Rs and its components. Infrared heaters were used to simulate a 2°C warming of the surface soil temperature. Deep collars (50 cm to exclude root growth) were inserted into soil to measure Rh: Ra, which was calculated by subtracting Rh from Rs. Average Rs and its components (Ra and Rh) were significantly stimulated by 21.5, 27 and 15.6%, respectively, in warmed plots from January 2011 to October 2013. The contribution of Rh to Rs decreased in the warmed plots because of the smaller relative increase in Rh than in Ra. Annual soil C release increased by 263 and 247 g C m−2 in 2011 and 2012, respectively. Stimulation in Ra and Rh was related to the significant increase in root biomass (0–50 cm) and in labile soil C in the deeper layer (40–50 cm). The temperature sensitivities (Q10) of Rs and its components all increased with larger values in Ra, followed by Rs and Rh. Our results suggest a positive feedback between soil C release and climatic warming in the permafrost region of the QTP.